(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
Apoptosis is one of markers considered in drug design including in treating cancers. Conventional treatments for cancer cause various side effects. One of possible alternatives is honey, an antioxidant driven by its phenolic and flavonoids content. This study aims to observe the effects of Malaysian Acacia honey in inhibiting breast cancer cell growth through apoptosis. Antioxidant properties of the honey were measured using total phenolic content (TPC) and total flavonoid content (TFC). Then, antiproliferative activity of the honey were observed using MTT assay. The honey exhibited IC50 at concentration of 5.5% (v/v). Further studies using TUNEL and live cell view revealed that Acacia honey induced apoptosis after 6 hours of treatment. Cell shrinkage, which is one of the apoptotic features, was observed as early as 2 hours, followed by the formation of apoptotic bodies within 6 hours of the honey treatment. Details of mechanism and actual compounds involved in displaying the results are being intensively studied.